Vagal Afferent Processing by the Paratrigeminal Nucleus - Driessen, Alexandria K. (Frontiers in Physiology, 2019)
The paratrigeminal nucleus is an obscure region in the dorsal lateral medulla, which has been best characterized as a collection of interstitial cells located in the dorsal tip of the spinal trigeminal tract. The paratrigeminal nucleus receives afferent input from the vagus, trigeminal, spinal, and glossopharyngeal nerves, which contribute to its long-known roles in the baroreceptor reflex and nociceptive processing. More recently, studies have shown that this region is also involved in the processing of airway-derived sensory information. Notably, these studies highlight an underappreciated complexity in the neuronal content and circuit connectivity of the paratrigeminal nucleus. However, much remains to be understood about how paratrigeminal processing of vagal afferents is altered in disease. The aim of the present review is to provide an update of the current understanding of vagal afferent processing in the paratrigeminal nucleus and to explore how dysregulation at this site may contribute to vagal sensory neural dysfunction during disease.